(untitled) (Stamford Journal of English, 2013)
Amitav Ghoshs first novel The Circle of Reason (1986) demonstrates the relationship between different discourses of knowledge (Science, History, Anthropology) and its colonial application to specific localities that authenticates key strategic policy to determine world trade and economy. In particular, the novel reflects how the emergence of science and textile mills shifts the paradigm of weaving world into the rubric of construction business. This paper focuses on how this manipulative change in world trade and economy predetermines the influx of people from one area to another with their existing skill (weaving) and profession. This paper examines three multicultural cities of three different localities that represent diasporic lives with all their struggle, potentiality, hybridity, mimicry and ambivalence. It will also highlight on how border-business, like trafficking, smuggling, is another important issue that creates newer trajectories for more profitable business (oil, bomb, gold, hashish) that encourages displacement of people. The character of Balaram, one of the major characters of part one of the novel, will be explained as a mimic character as he represents the colonial application of science in this subcontinent. Balaram has been presented according to Homi K. Bhabhas Of Mimicry and Man: The ambivalence of colonial discourse (121). And the diasporic cities like Lalpukur, al-Ghazira and El Oued can be 187 explained from Homi K. Bhabhas, Cultural Diversities and Cultural Differences. Stamford Journal of English; Volume 6; Page 186-202 DOI: http://dx.doi.org/10.3329/sje.v6i0.13913